Dried Baby Formula as a Source of Opportunistic Members of Enterobacteriaceae for Infants - Ibrahim, AS; Fouad Saad , M; Moustafa Hafiz , N (Journal of the Hellenic Veterinary Medical Society, 2023)
For evaluating the prevalence of Enterobacteriaceae in baby formulas, we examined 60 different samples of powdered infant milk formula and milk-cereal based infant formula that is recommended for first-day birth and from 6-month age, respectively, and collected from various supermarkets, shops, and pharmacies. Six (20.0%) and thirteen (43.3%) powdered infant milk formulas and milk-cereal based infant formulas, respectively, were contaminated by different Enterobacteriaceae involved Enterobacter cloacae ssp. cloacae, Pantoea spp., Enterobacter hormaechei, and Raoultella ornithinolytica, which were identified using traditional biochemical tests and the vitek2 compact system. Only five samples of investigating milk-cereal based infant formula type have coliforms count of 4 MPN/g. All species were susceptible to gentamycin, while all were resistant to cephalothin antibiotics. Eventually, 20.0 % of powdered infant milk formula samples were unacceptable referred to Egyptian standards (2072/2006) and most of the comparable international standards. In the study, we proved the contamination of powdered milk baby formula by Enterobacteriaceae, which mainly causes health problems in immature and immunocompromised infants. The dried infant formula factories are more needful for good hygiene and safety systems applications. This study is one of the fewest studies conducted in Egypt to isolate Enterobacteriaceae members from dried foods; especially milk-cereal based infant formula.